Quasimomentum of an elementary excitation for a system of point bosons under zero boundary conditions - Tomchenko, M.D. (Reports of the National Academy of Sciences of Ukraine, 2019)
As is known, an elementary excitation of a many-particle system with boundaries is not characterized by a definite momentum. We obtain the formula for the quasimomentum of an elementary excitation for a one-dimensional system of N spinless point bosons under zero boundary conditions (BCs). In this case, we use Gaudin's solutions obtained with the help of the Bethe ansatz. We have also found the dispersion laws of the particle-like and hole-like excita tions under zero BCs. They coincide with the known dispersion laws obtained under periodic BCs.